Securitization of China in the NATO discourse in the late 2010s— early 2020s: Towards a global collective identity - Yu. Yu. Melnikova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
By the early 2020s, the NATO representatives have adopted an increasingly alarmist rhetoric regarding China’s strengthening positions in the international relations. In 2022, the PRC was officially qualified as a ‘systemic challenge’ to the countries of the alliance. These attempts to securitize the Chinese factor in the NATO’s discourse are particularly noteworthy since they can hardly be rationalized by traditional military-political, economic or ideological reasons. The author argues that these reasons stem from the NATO’s search for a new, global identity. In order to test this hypothesis, the article traces the evolution of the alliance’s collective self-representations from the Cold War period up to the present day. The author shows that during the Cold War, when NATO positioned itself as a military-political alliance aimed at deterring the ‘Soviet threat’, the alliance’s relations with China developed steadily and constructively despite political and ideological differences. In the post-bipolar period, the Chinese factor has lost its importance even more, as NATO was actively considering the idea of repositioning itself as a ‘security community’. Attention to the PRC in the NATO discourse increased significantly in the 2010s, when the alliance set a course towards a radical expansion of its mandate in international relations and self-representation as a global security actor. However, as the author emphasizes, during this period there still have been no attempts to securitize China, and relations between the PRC and NATO were marked by positive dynamics. The shift in the perception of the PRC in the NATO’s official discourse took place in the second half of the 2010s — early 2020s and stemmed from the apparent difficulties in asserting the global identity of the alliance and the growing great-power rivalry in the international arena. From this perspective, increasing efforts to securitize the PRC could be ascribed to the continuous evolution of the alliance’s collective identity and the desire of its leaders to close ranks in the face of new strategic challenges. However, the author shows that the deterioration of relations between NATO member states and Russia, a traditional ‘significant other’ for the alliance, renders meaningless any further attempts to securitize China, which continue still more by inertia.